Fighting words : imperial censorship and the Russian press, 1804-1906 - Ruud, Charles A., 1933- (University of Toronto Press, 2009)
First published in 1982, Fighting Words focuses on the most common form of censorship in Imperial Russia: the governmental system that screened written works before or after publication to determine their acceptability.